Financial Planning as a Management Model - Casanueva-Yáñez, Galvarino; León-Bustos, Yedica; Torres-Vásquez , Jorge; Pillaca-Vilca, Luis Antonio; Pavez-Bravo, Claudio; Rincón-Moreno, Mauricio; Vilca-Ccolque, José Yudberto; Rengifo-Lozano, Raúl (Journal of Ecohumanism, 2024)
This article addresses the shortcomings in the strategic planning of companies and presents the conclusions about their possible solutions that are crucial to ensure their sustainability and growth. The implementation of this type of solution will allow companies to improve their strategic planning, ensure their financial sustainability and position themselves competitively in the market. It also emerges that the adoption of sound financial practices and the use of appropriate management tools are essential to face the challenges of the business environment and take advantage of growth opportunities.